Estimation of the chronological age based on the mineralization of the third lower molar in the andean population - Rodríguez, Andrea (2021)
Objective: To determine the level of mineralization of the third lower molar according to chronological age using the Demirjian method in panoramic digital radiographies of Andean patients. Material and methods: A correlational study was carried out analyzing 706 digital panoramic radiographies in the Unidad Académica de Salud y Bienestar de la Universidad Católica de Cuenca Ecuador, in the period 2015-2016. The patients were between 6 and 22 years of age. A total of 1412 third molars (4.8 and 3.8) were evaluated. Results: A first descriptive analysis showed a strong correlation (Rho=0.99) between chronological age and the level or degree of mineralization of the lower third molar. In both studied pieces the beginning of the formation of the third molar was given in average at 8,13 years and finished at 20,41 years. The stages that showed greater coincidence in both sexes and in both pieces were B, C, F, G and H and the stages with less coincidence were the stages A, D, E. Conclusions: According to the results we can suggest that the Demirjian method is a useful tool to determine the chronological age based on the mineralization of the third molars, with an error of +/- 1.2 months so it is possible to be used for the estimation of the age in forensic evaluations.